Delayed open abdomen closure using a combination of acellular dermal matrix and skin graft in Korea: a case report - Kim, Yoonseob; Kim, Tae Ah; Hahn, Hyung Min; Kang, Byung Hee (Daehan oe'sang haghoeji, 2023)
Delayed closure of an open abdomen (OA) is a clinically challenging task despite its various modalities. It is substantially more difficult when the duration of OA treatment is prolonged due to a patient's condition. We introduced the management of a patient who had a delayed OA treatment spanning approximately 3 months due to severe abdominal contamination. The 64-year-old male patient had an injured pelvis pressed by a road roller. After visiting a trauma center, the patient initially underwent damage control surgery and OA management; however, early primary abdominal closure failed due to severe peritonitis. After negative pressure wound therapy for several months, an acellular dermal matrix graft followed by a skin graft were successfully used as treatments. A combination of acellular dermal matrix graft, negative pressure wound therapy, and skin graft techniques is a considerable management sequence for patients subjected to delayed OA treatment.